2022
DOI: 10.1021/acschemneuro.2c00097
|View full text |Cite
|
Sign up to set email alerts
|

Sleep–Wake Disorders in Alzheimer’s Disease: A Review

Abstract: Alzheimer’s disease (AD) is a multifactorial disease, and it has become a serious health problem in the world. Senile plaques (SPs) and neurofibrillary tangles (NFTs) are two main pathological characters of AD. SP mainly consists of aggregated β-amyloid (Aβ), and NFT is formed by hyperphosphorylated tau protein. Sleep–wake disorders are prevalent in AD patients; however, the links and mechanisms of sleep–wake disorders on the AD pathogenesis remain to be investigated. Here, we referred to the sleep–wake disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 168 publications
0
12
0
Order By: Relevance
“…In this way, we were able to (i) determine how ANP interferes with Aβ aggregation pathways starting from different aggregated species by ThT (Figure 3a) and (ii) identify which aggregated species (Aβ monomers, oligomers, and fibrils) are more favorable to interact with ANP by SPR (Figure 3e−g). ThT kinetics curves in Figure 3a clearly showed that in all cases, the addition of ANP of different concentrations (5,10,20 AFM and far-UV CD spectroscopy were also performed to confirm and understand the ANP-induced fibril inhibition and structural transition of different Aβ seeds. As shown in Figure 3c, 20 μM pure Aβ formed a large number of mature fibrils with an average height/length of 33/605 nm (black box), while the co-incubation of 10 μM ANP with 1 h-(red box), 5 h-(blue box), and 11 h-(green box) Aβ seeds led to obvious fibril inhibition and disaggregation, as visualized by a few small spherical aggregates or short fibrils.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In this way, we were able to (i) determine how ANP interferes with Aβ aggregation pathways starting from different aggregated species by ThT (Figure 3a) and (ii) identify which aggregated species (Aβ monomers, oligomers, and fibrils) are more favorable to interact with ANP by SPR (Figure 3e−g). ThT kinetics curves in Figure 3a clearly showed that in all cases, the addition of ANP of different concentrations (5,10,20 AFM and far-UV CD spectroscopy were also performed to confirm and understand the ANP-induced fibril inhibition and structural transition of different Aβ seeds. As shown in Figure 3c, 20 μM pure Aβ formed a large number of mature fibrils with an average height/length of 33/605 nm (black box), while the co-incubation of 10 μM ANP with 1 h-(red box), 5 h-(blue box), and 11 h-(green box) Aβ seeds led to obvious fibril inhibition and disaggregation, as visualized by a few small spherical aggregates or short fibrils.…”
Section: Resultsmentioning
confidence: 95%
“…As a multifactorial and chronic disease, different genetic and nongenetic factors are reported to contribute to the pathogenesis of AD. Genetic factors include the inherited APP mutants (presenilin 1, presenilin 2), apolipoprotein E, neurotransmitters, adenosine triphosphate (ATP)-binding cassette transporter, bridging integrator protein 1, and others, while nongenetic factors (i.e., exogenous factors) includes cerebrovascular diseases, type 2 diabetes, brain trauma, microbial infection, stroke, sleep disorders, metabolic disorders, obesity, and others. Clinical studies have shown that only less than 1% AD patients have inherited genetic deficiency, while AD in most patients (>95%) derives from the complicated interplay between multiple genetic and nongenetic factors. , …”
Section: Introductionmentioning
confidence: 99%
“…According to keyword analysis, research has focused on the effects of degenerative diseases on sleep, such as Parkinson’s disease ( Postuma et al, 2015 ; Krause et al, 2017 ; McKeith et al, 2017 ; Postuma et al, 2019 ), Alzheimer’s disease ( Mizrahi-Kliger et al, 2022 ; Sun et al, 2022 ), and small vessel disease ( Semyachkina-Glushkovskaya et al, 2020 ; Li et al, 2022 ). We speculate that this may be related to the aging of the population and the fact that the elderly are more likely to develop sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies in humans have shown increases in Aβ plaque formation in individuals with poor sleep (Spira et al, 2013; Spira et al, 2014). Moreover, increased Aβ aggregation also increases sleep disturbances exacerbating disease progression (reviewed in [Chen et al, 2021; Sun et al, 2022]). Sleep deprivation may, in part, increase the risk of neurological diseases through decreased clearing of metabolic waste via the glymphatic system (reviewed in [Achariyar et al, 2016; Bishir et al, 2020; Rasmussen et al, 2018]).…”
Section: Future Directionsmentioning
confidence: 99%